PBL-based online-offline hybrid teaching in nursing education: enhancing self-regulated learning and teaching effectiveness in China - Feng, Xiaoyan; Zhou, Ying; Liao, Bizhen (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate students’ satisfaction and learning outcomes associated with a blended online and offline teaching method based on problem-based learning (PBL).DesignA total of 238 third-year undergraduate nursing students from two classes participated. Each class was divided into eight groups, with 14 to 15 students per group. Eight teachers were involved. A cross-sectional survey was conducted among students after class.MethodsHypertensive disorders of pregnancy were chosen as the teaching cases. Teachers uploaded teaching resources to Superstar Learning App for 1 week of online self-regulated learning (SRL). During the offline class, each group addressed two clinical questions through presentations, simulated scenarios and role-playing exercises. After course, students were invited to complete an anonymous satisfaction questionnaire. A descriptive cross-sectional design was employed, a descriptive analysis of participants was conducted, and factors influencing teaching effectiveness were analyzed.ResultsOverall, 79.82% of students expressed greater satisfaction with this blended method compared to traditional teaching approaches, 95.07% of students gave positive feedback on the course, and 92.82% reported that their learning outcomes either met or exceeded expectations. Students who engaged intensively in collecting, analyzing, and organizing information during the online phase, or who devoted ≥5 h to online learning, were significantly more likely to achieve or surpass their learning expectations (p < 0.05). Although participation in activities did not significantly affect learning outcomes (p > 0.05), it did influence students’ evaluation of teaching (p < 0.05). A significant difference was also observed between the two classes in their session evaluations (p < 0.05).ConclusionThe blended PBL approach was associated with higher student satisfaction in the Obstetrics and Gynecology Nursing course. Class participation correlated positively with evaluations and outcomes. While active participants achieved expected results, less participative students also attained comparable outcomes through alternative methods. Although pre-class preparation time predicted learning effectiveness, efficiency was equally significant. Adopting a student-centered, PBL-oriented approach with diversified resources is recommended to address individual needs, enhance satisfaction, and develop SRL skills. This model promotes SRL by encouraging students to assess and adjust their learning strategies, thereby meeting diverse needs and supporting personalized development.